Precipitation of Fine Carbides, Transformation of the Retained Austenite and Corrosion Properties on EN-31 Steel by Cryogenic Treatment Process - Sri Siva, R.; Shunmuga Priyan, M. (Asian Review of Mechanical Engineering, 2022)
Investigate of precipitation carbides transformation of the retained austenite and corrosion properties on EN-31 steel by cryogenic treatment method. In this work to identify the percentage of retained austenite and corrosion rate, was presented on EN 31 bearing steel by which cryogenic treatment process. Further, the hardness values of CHT and DCT were compared by using the microstructure view of the CHT and DCT samples. The optimized cryotreated samples were prepared for metallographic examination as per ASTM E3-01. Then the specimen was subjected to factor level setting like cooling rate, soaking period, soaking temperature and tempering temperature at various conditions. Moreover, the precipitation of fine carbides and the transformation of retained austenite to martensite showed considerable variations in the hardness of the optimized DCT samples compared to the CHT samples. The mean hardness value of this sample is 861HV and 19.20%, 847HV and 17.25%, 838HV and 17.10%, 857HV and 18.40%, 790HV and 13.45% improvement in the hardness compared to CHT.